PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VII - Vivi Amanda Firdaus; Yulia Haryono; Zulfitri Aima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine whether the application of the problem based learning (PBL) learning model is better than the understanding of mathematics concepts of students with conventional learning models in grade V/II students of SMP Negeri 5 Kubung. The type of research used is true experimental design using a posttest only control group design. The population in the study consisted of all grade VII students of SMPN 5 Kubung. The sample was selected using a random sampling method. The instrument used to collect data in this study was a post-test in the form of essay questions. Data analysis was carried out using a one-tailed t-test (right side). Based on the results of the hypothesis test, it was pbtained t count = 2,121 and t table = 1.681 at a significance level of a = 0.05, so t count> t table, so the hypothesis can be accepted. Based on the results of the study,it shows that students' understanding of mathematics concepts by applying the PBL model is better than students' understanding of mathematics concepts using conventional learning models.